2020
DOI: 10.1021/acsnano.0c06649
|View full text |Cite
|
Sign up to set email alerts
|

Parallel-Stacked Flexible Organic Light-Emitting Diodes for Wearable Photodynamic Therapeutics and Color-Tunable Optoelectronics

Abstract: Deformable organic light-emitting diode (OLED) based optoelectronic devices hold promise for various wearable applications including biomedical systems and displays, but current OLED technologies require high voltage and lack the power needed for wearable photodynamic therapy (PDT) applications and wearable displays. This paper presents a parallel-stacked OLED (PAOLED) with high power, more than 100 mW/cm 2 , at low voltage (<8 V). The current dispersion ratio can be tuned by optimizing the structure of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 38 publications
1
78
0
Order By: Relevance
“…Newborn babies often go through blue-light therapy for prevention of jaundice, for example. Phototherapies may be classified into the following: (i) photobiomodulation (PBM), which is to use lowintensity light to modulate cellular function; (ii) photothermal treatment, which is to use light to induce thermal ablation of cells to be treated; and (iii) photodynamic therapy (PDT), which employs light to activate photosensitizer to produce reactive oxygen species (ROS) to attack malignant cells [6].…”
Section: Oleds For Healthcare Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborn babies often go through blue-light therapy for prevention of jaundice, for example. Phototherapies may be classified into the following: (i) photobiomodulation (PBM), which is to use lowintensity light to modulate cellular function; (ii) photothermal treatment, which is to use light to induce thermal ablation of cells to be treated; and (iii) photodynamic therapy (PDT), which employs light to activate photosensitizer to produce reactive oxygen species (ROS) to attack malignant cells [6].…”
Section: Oleds For Healthcare Applicationsmentioning
confidence: 99%
“…Recently, Jeon et al has explored the feasibility of OLEDs for PDT [6]. It was shown that high-intensity illumination is far more effective in creation of ROS.…”
Section: Oleds For Healthcare Applicationsmentioning
confidence: 99%
“…With the ongoing development of the Internet of Things (IoT), organic light emitting diodes (OLEDs) are being utilized in a wide range of platforms including wearable displays, automotive displays, and see-through displays due to their attractive properties such as high transparency, low power consumption, light weight, and outstanding deformability. (1)(2)(3)(4)(5)(6)(7) However, such applications expose OLEDs to various environmental factors such as high temperature/humidity or rainy weather. Despite this, the reliability of OLEDs has not been characterized yet under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…d,e) Stacked red-emitting OLEDs with parallel connection of subunits reaching high power output and improved device lifetime. Reproduced with permission [144]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…This can attack nearby cells. Reproduced with permission [144]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%